Hyaluronic acid and albumin based nanoparticles for drug delivery - Lei, Can; Liu, Xiu-Ran; Chen, Quan-Bing; Li, You; Zhou, Jia-Li; Zhou, Ling-Yue; Zou, Tao (Journal of controlled release, 2021)
Albumin, a multifunctional protein, is widely used to prepare nanocarriers. Hyaluronic acid (HA) is a natural glycosaminoglycan that can specifically bind receptors, such as cluster of differentiation-44. Therefore, HA is commonly used as ligands for the surface modification of versatile nanocarriers. The combined utilization of albumin and HA as nanocarriers shows outstanding superiorities including efficient targeting, reducible particle size, pH and/or hyaluronidase sensitive drug release, combining capacity for various drugs, biocompatibility, non-immunogenicity, biodegradability and high stability. However, to the best of our knowledge, HA and albumin based nanoparticles have not been reviewed for drug delivery so far. This review involves the introduction of the essential information of HA and albumin as well as a brief presentation of the preparation methods of HA and albumin based nanocarriers. Moreover, the application of HA and albumin based nanoparticles as drug delivery carriers in tumors, joints, vitreum and skin tissue is systematically discussed with the potential and prospect in combined therapy and theranostics. In addition, the unique advantages of the HA and albumin based nanoparticles and their contributions to the improvement of drug delivery systems are further expounded in detail. [Display omitted] •Structural features and intrinsic properties of hyaluronic acid and albumin.•Significance and preparation of hyaluronic acid and albumin based NPs.•Applications of hyaluronic acid and albumin based NPs.•Summary and prospects of hyaluronic acid and albumin based NPs.